PENGARUH REFERRAL MARKETING, ONLINE CUSTOMER REVIEW DAN PROMOSI TERHADAP BUYING DECISION MELALUI BUYING INTEREST SHOPEE FOOD DI WILAYAH SURABAYA BARAT - Devi Rahmawati; Fitra Mardiana (Jurnal Ekonomi, Bisnis dan Social, 2023)
During the pandemic period in the previous year in order to protect themselves from the viral outbreak that was rampant in the city, the Shopee company issued a new feature, namely the Shopee Food feature which can make it easier for people to buy food by taking away, in addition to making it easier for people to shop that way. keep people from crowding. In this study took a sample of 100 community respondents in the West Surabaya Region. The sampling technique used was non-probability sampling and the sampling method was accidental sampling. The analytical method used is path analysis. The results of this study indicate that referral marketing has a significant effect on buying interest, online customer reviews have no significant effect on buying interest, promotions have no significant effect on buying interest, referral marketing has no significant effect on buying decisions, online customer reviews have a significant effect on buying decisions, promotion has a significant effect on buying decisions, buying interest has no significant effect on buying decisions.